2011
DOI: 10.1515/nor-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Presidential Debates

Abstract: One of the most used theories in the research of political debates is the functional theory of campaign discourse. However, the theory has been criticized for being too culturally limited. In the present article, a Finnish presidential debate is analyzed from the perspective of functional theory. The goal is to critically evaluate the applicability of functional theory to the analysis of Finnish political campaigning. The results show that a Finnish presidential debate differs in many ways from an American pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
(15 reference statements)
1
19
0
1
Order By: Relevance
“…Cmeciu and Patrut (2010) agreed with this critique, arguing that political campaign discourse is not consistent across borders and cultures; indeed, their study of the 2009 Romanian presidential debates revealed the debates were not focused on acclaims and policy, as argued by the functional theory, but instead on attacks and defences. Also Hrbková and Zagrapan's (2014) research of the 2012 election debates in Slovakia reached similar conclusions, arguing the categories of content analysis should be expanded as with the current categories more than 30 percent of the content of the debates would be excluded from the analysis -an argument also made by Isotalus (2011). Nevertheless, from the content analysed, acclaims were still the most common category, followed by attacks, which means the results reached in Slovakia are at least somewhat similar to those reached in the United States.…”
Section: Literature Reviewmentioning
confidence: 85%
See 4 more Smart Citations
“…Cmeciu and Patrut (2010) agreed with this critique, arguing that political campaign discourse is not consistent across borders and cultures; indeed, their study of the 2009 Romanian presidential debates revealed the debates were not focused on acclaims and policy, as argued by the functional theory, but instead on attacks and defences. Also Hrbková and Zagrapan's (2014) research of the 2012 election debates in Slovakia reached similar conclusions, arguing the categories of content analysis should be expanded as with the current categories more than 30 percent of the content of the debates would be excluded from the analysis -an argument also made by Isotalus (2011). Nevertheless, from the content analysed, acclaims were still the most common category, followed by attacks, which means the results reached in Slovakia are at least somewhat similar to those reached in the United States.…”
Section: Literature Reviewmentioning
confidence: 85%
“…In recent years, however, the functional theory of political campaign discourse has been applied to several elections in various countries outside of the US. So far, functional theory has been used to analyse political campaign discourse in Slovakia (Hrbková & Zagrapan, 2014), the United Kingdom (Benoit & Benoit-Bryan, 2013), France (Choi & Benoit, 2013), Spain (Herrero & Benoit, 2009), Israel (Benoit & Sheafer, 2006), Taiwan (Benoit, Wen, & Yu, 2007), Romania (Cmeciu & Patrut, 2010), Ukraine (Benoit & Klyukovski, 2006), Germany (Benoit & Hemmer, 2007), Korea (Lee & Benoit, 2004, 2005, Finland (Isotalus 2010(Isotalus , 2011, Canada (Benoit, 2011;Benoit & Henson, 2007), and Australia (Benoit & Henson, 2007). Applying functional theory to research the political campaign discourse in countries other than the US has raised the question of whether the theory is too culturally limited to be useful in political systems different from that of the US.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations